Iklim Organisasi, Gaya Kepemimpinan Partisipatif dan Beban Kerja terhadap Komitmen Organisasi PT Equityworld Futures - Dwi Wulansari (STIE Widya Manggala, 2023)
The study aims to analyze the influence of organizational climate on participatory leadership styles and workload on organizational commitment. The population in this study were 122 employees of PT Equityworld Futures. The sample size is determined by using the slovin formula so that the number of respondents in this research is 55 employees. The analysis tool used in this study is multiple linear regression eith help of SPSS verssion . the result show that the organizational climate, participatory leadership style and workload had a significant effect on organizational commitment.